On the Origin of the Ideality Factor in Perovskite Solar Cells - Ardalan Armin (Advanced Energy Materials, 2020)
The measurement of the ideality factor (n id) is a popular tool to infer the dominant recombination type in perovskite solar cells (PSC). However, the true meaning of its values is often misinterpreted in complex multilayered devices such as PSC. In this work, the effects of bulk and interface recombination on the n id are investigated experimentally and theoretically. By coupling intensity‐dependent quasi‐Fermi level splitting measurements with drift diffusion simulations of complete devices and partial cell stacks, it is shown that interfacial recombination leads to a lower n id compared to Shockley–Read–Hall (SRH) recombination in the bulk. As such, the strongest recombination channel determines the n id of the complete cell. An analytical approach is used to rationalize that n id values between 1 and 2 can originate exclusively from a single recombination process. By expanding the study over a wide range of the interfacial energy offsets and interfacial recombination velocities, it is shown that an ideality factor of nearly 1 is usually indicative of strong first‐order non‐radiative interface recombination and that it correlates with a lower device performance. It is only when interface recombination is largely suppressed and bulk SRH recombination dominates that a small n id is again desirable.